A case study on the promotional activities in Kazzponic Sdn Bhd / Saifuddin Fahro Rozi - Fahro Rozi, Saifuddin (2009)
Kazzponic Sdn Bhd is an organization founded by a bumiputra which operates in selling liquid fertilizer and hydroponics set and services. The company is striving hard to survive in the market that is increasing of competition. During the industrial training, it is found that most of that the company is very lack in a certain areas. One of the most significant areas is that they are lack of utilize the promotion mix. Promotional mix is currently the most important strategic tools taken by most successful companies in the market. The promotion mix which are comprises advertising, personal selling, sales promotion, direct marketing and public relation. The purpose of the study is to determine issues of the company, what they practiced, and the gap identification between the theory of Promotion mix activities and what the company practiced. This report outlining the introduction, issues, literature, research methodology, findings, and recommendation based on observation, company report, and interview to several employees in Kazzponic Sdn Bhd. For the purpose of this dissertation, the qualitative research was used; the researcher used an interview method as a tool to get the information from the Kazzponic Sdn Bhd staff. This research also used secondary data as a tool for getting the information about Kazzponic and other information especially on promotion mix matters. From this study, it can be conclude that most of the factors that influence the sales of company products are well implemented of promotional activities by the company.